Clapping dan Vibration Meningkatkan Bersihan Jalan Napas pada Pasien ISPA - Andi Muh. Faisal; Najihah Najihah (Jurnal Penelitian Kesehatan SUARA FORIKES, 2020)
One of the nursing diagnoses in upper respiratory tract infection is the ineffectiveness of airway clearance, and interventions that can be planned to improve airway clearance, namely chest physiotherapy (clapping and vibration). This study aims to determine the effectiveness of providing clapping and vibration for airway clearance in upper respiratory tract infection patients in Labuang Baji Regional Hospital Makassar. This research was an experimental research with one group pretest posttest design. Samples in the study of 16 patients with upper respiratory tract infection were determined by accidental sampling technique. Data were collected using an observation sheet. Data analysis used Mc Nemar test. The results showed that clapping and vibration were effective in increasing airway clearance (p = 0.000) and effective against indicators of airway clearance, namely decreased respiratory frequency (p = 0.031), decreased sputum production (p = 0,000) and ronchi (p = 0.001). It was concluded that clapping and vibration were effective in increasing airway clearance in upper respiratory tract infection patients. Keywords: clapping and vibration; clearance of the airway; upper respiratory tract infection ABSTRAK Salah satu diagnosa keperawatan yang muncul pada penyakit ISPA adalah ketidakefektifan bersihan jalan napas, dan intervensi yang dapat direncanakan untuk meningkatkan bersihan jalan napas yaitu pemberian fisioterapi dada (clapping dan vibration). Penelitian ini bertujuan untuk mengetahui efektifitas pemberian clapping dan vibration terhadap bersihan jalan napas pada pasien ISPA di RSUD Labuang Baji Kota Makassar. Penelitian ini merupakan penelitian eksperimen dengan one group pretest posttest design. Sampel dalam penelitian 16 pasien ISPA yang ditentukan dengan teknik accidental sampling. Data dikumpulkan menggunakan lembar observasi. Analisis data menggunakan uji Mc Nemar. Hasil penelitian menunjukkan bahwa clapping dan vibration efektif meningkatkan bersihan jalan napas (p=0.000) dan efektif terhadap indikator besihan jalan napas, yaitu penurunan frekuensi pernapasan (p=0.031), penurunan produksi sputum (p=0.000) dan ronchi (p=0.001). Sehingga disimpulkan bahwa clapping dan vibration efektif meningkatkan bersihan jalan napas pada pasien ISPA. Kata kunci: clapping dan vibration; bersihan jalan napas; ISPA